Pengaruh Karakteristik Audit, Struktur Kepemilikan dan Return on Investment terhadap Prediksi Kebangkrutan Perusahaan Perdagangan - Sariyanto Sariyanto; Nova Yesyca Naipospos (Politeknik Ganesha Medan, 2021)
This study aims to determine the effect of the characteristics of the audit committee, ownership structure and return on investment on the prediction of bankruptcy in trading companies listed. The research methodology used is descriptive quantitative method, and the data sources are secondary data. The population of this study is 49 trading companies listed on the Indonesia Stock Exchange for the 2017-2018 period and 16 companies which sample. The sample technique used in this study was purposive sampling. The data analysis technique of this research is multiple regression analysis using hypothesis testing, namely partial test (t test), simultaneous test (F test) and the coefficient of determination test. The results of the study partially show that the characteristics of the audit committee have no significant effect on the prediction of bankruptcy with a significance test of -3.232 <2.014. Ownership structure has a significant effect on bankruptcy predictions with a value of 4.045> 2.014. Return on investment has no significant effect on bankruptcy predictions with a value of 1.325 <2.014. The results of the research simultaneously show that the characteristics of the audit committee, ownership structure and return on investment on the prediction of bankruptcy in trading companies listed on the Indonesia Stock Exchange have a significant effect with a value of 7.347> 2.81. Square obtained from the results of this study). The conclusion from the results of this study shows that partially the characteristics of the audit committee.